Moyamoya Syndrome Associated with Basal Meningioma Successfully Treated by the Modified Transsphenoidal Approach: Case Report - Yoshikazu Ogawa; Miki Fujimura; Teiji Tominaga (Journal of Neurological Surgery Reports, 2014)
Abstract